Delivery of mitoxantrone using a plant virus-based nanoparticle for the treatment of glioblastomas - Lam, Patricia (J Mater Chem B, 2018)
Mitoxatrone (MTO), an antineoplastic chemotherapeutic, has potent activity against the most common and agressive type of primary brain tumor, glioblastoma multiforme (GBM). However, its poor penetration through the blood brain barrier, and cardiotoxic side effects from systemic delivery limit its effectiveness for clinical treatment. To address these limitations, we utilize a plant virus-based nanoparticle, cowpea mosaic virus (CPMV), to deliver MTO to treat GBM. In this work, we loaded MTO into the interior cavity of CPMV (CPMV-MTO) through diffusion through its pores. We report the uptake of CPMV-MTO in glioma cells and demonstrate its cytotoxic effects in vitro as a solo therapy, and in combination with tumor necrosis factor-related apoptosis-inducing ligand (TRAIL). These results reveal the potential for this plant virus-based nanoparticle platform for the treatment of GBM.